Melatonin prevents neural tube defects in the offspring of diabetic pregnancy. Issue 4 (17th October 2015) - Liu, Shangming; Guo, Yuji; Yuan, Qiuhuan; Pan, Yan; Wang, Liyan; Liu, Qian; Wang, Fuwu; Wang, Jingjing; Hao, Aijun
Abstract: Melatonin, an endogenous neurohormone secreted by the pineal gland, has a variety of physiological functions and neuroprotective effects. However, its protective role on the neural tube defects (NTDs) was not very clear. The aim of this study was to investigate the effects of melatonin on the incidence of NTDs (including anencephaly, encephalocele, and spina bifida) of offspring from diabetic pregnant mice as well as its underlying mechanisms. Pregnant mice were given 10 mg/kg melatonin by daily i.p. injection from embryonic day (E) 0.5 until being killed on E11.5. Here, we showed that melatonin decreased the NTDs (especially exencephaly) rate of embryos exposed to maternal diabetes. Melatonin stimulated proliferation of neural stem cells (NSCs) under hyperglycemic condition through the extracellular regulated protein kinases (ERK) pathway. Furthermore, as a direct free radical scavenger, melatonin decreased apoptosis of NSCs exposed to hyperglycemia. In the light of these findings, it suggests that melatonin supplementation may play an important role in the prevention of neural malformations in diabetic pregnancy.